2019
DOI: 10.3390/ijerph16162832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Occupational Exposure to Perchlorethylene in a Group of Italian Dry Cleaners Using Noninvasive Exposure Indices

Abstract: Recent data suggest a general trend in decreased occupational exposure to perchlorethylene (PCE) in the dry-cleaning sector. The aims of this study were to confirm this trend to lower exposure levels in a group of Italian dry cleaners and to evaluate the current occupational PCE exposure in these works using noninvasive biological indices. Environmental exposure was assessed by personal sampling in 60 operators working in 21 dry cleaning shops in North Italy. PCE in the exhaled alveolar air (PCEalv), urinary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…[ 24,25 ] Previous studies have shown that this solvent has the potential to damage vital organs such as the liver and kidneys. [ 2,26 ] Our results showed that the levels of ALT and AST as liver enzymes in dry cleaning workers are higher than in the control group. However, no significant difference was observed in BUN and creatinine levels between the two groups.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…[ 24,25 ] Previous studies have shown that this solvent has the potential to damage vital organs such as the liver and kidneys. [ 2,26 ] Our results showed that the levels of ALT and AST as liver enzymes in dry cleaning workers are higher than in the control group. However, no significant difference was observed in BUN and creatinine levels between the two groups.…”
Section: Discussionmentioning
confidence: 64%
“…Oxidative stress and mitochondrial damage are the mechanisms of TCA toxicity. [14,15,26] Physiologically, oxidative stress is a condition in which the balance between oxidants (ROS) and antioxidants status is disturbed by exposure to various factors. [27,28] To examine the relationship between exposure to various compounds and oxidative stress, parameters such as ROS, LPO, and intracellular antioxidant enzymes (GSH) are evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Modenese et al conducted personal air sampling as well as biological sampling via exhaled air measurements and urine concentration measurements. The study population included 21 dry cleaning shops and 60 workers ( 69 ). Personal passive samplers were placed on each worker for an entire eight-hour work shift, and alveolar air and urine samples were collected at the end of the work shift ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study population included 21 dry cleaning shops and 60 workers ( 69 ). Personal passive samplers were placed on each worker for an entire eight-hour work shift, and alveolar air and urine samples were collected at the end of the work shift ( 69 ). Results of personal air sampling showed a mean concentration of 17.0 mg/m ³ (SD: 18.5 mg/m ³ ) and a range of 0.1–86.0 mg/m ³ within the established OSHA and ACGIH OEL ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the previous study which had suggested a weak but dose-related effect of PERC on the kidney of the dry-cleaning workers and it considered glutamine synthetase in urine as the most reliable biomarkers of renal changes in human exposed to low level of PERC as it could indicate a specific effect of this solvent on the proximal tubules (9) . Recent study emphasized on urine sample as another non-invasive biomarker for detection and evaluation of PERC in urine which might explain the potential deleterious effect of PERC on renal system (23) .…”
Section: Parametersmentioning
confidence: 99%